Strategi Pengembangan Lada Hitam Di Lampung Timur Menuju Ketahanan Pangan Dan Ekonomi - Adieshiya Febriyani; Erlin Kurniati (SUAN PUBLISHER, 2024)
This study aims to formulate an appropriate black pepper development strategy to increase its added value, competitiveness, and contribution to food security and the local economy. The method used in this research is a descriptive qualitative approach supported by SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). Data were collected through interviews with pepper farmers, village officials, and related agencies, as well as field observations. Next, an IFAS and EFAS matrix was developed to identify internal and external factors affecting black pepper development. The results of the analysis show that the main strengths lie in the experience of farmers and the potential for large areas of land, while the main weaknesses are limited technology and access to financing. On the other hand, development opportunities come from global market demand and government policy support, while the main threats come from climate change and market competition. Based on the position in the SWOT matrix, the development strategy of East Lampung black pepper is in quadrant I (aggressive strategy), which is to utilize strengths to seize opportunities. Strategies that can be applied include increasing the capacity of farmers through training, expanding market access with quality certification, and strengthening farmers' economic institutions. This strategy is expected to increase farmers' independence, strengthen food security, and drive the local economy in a sustainable manner.